History of Christianity in India - Vineeth, V F (Journal of Dharma, 1986)
A. M. Mundadan, History of Christianity in India, Vol. I. From the beginning up to the Middle of the Sixteenth Century, Bangalore: TPI; 1984. pp. 567 txxiv.